SAXON AGE - Scott, A. F. (Arthur Finley) ([S.l.])
1 online resource
Keywords: The Saxon Age (1979) presents a vivid portrait of the daily life of Saxon England. Using the first hand evidence of contemporary writers, artists and craftsmen, the book conveys the mood and style of the Saxons from the royal court to a peasant's hut. A wealth of information is offered, extending over five hundred years. Chronologically presented, many diverse aspects of life are covered - towns, family, education, the arts, sports and pastimes, health, work and wages, religion, law and crime, historic events, warfare and happenings on the sea.